Silent Carriers: The Hidden Threat of Antibiotic-Resistant Staphylococcus aureus in Retail Seafood Across Poland’s Tri-City Area - Anita Kukułowicz; Izabela Steinka; Aleksandra Szelągowska (Antibiotics, 2025)
Background/objectives: Antibiotic-resistant Staphylococcus aureus poses a significant risk to food safety and public health, particularly through the consumption of contaminated seafood. This study aimed to assess the presence and antibiotic resistance of S. aureus in seafood sold in the Tri-City area of Poland, addressing a knowledge gap regarding the region. Methods: Seafood samples (n = 89) were categorized according to their origin: domestic—Poland (PL), European countries (ECs), and Asian countries (ACs). S. aureus was isolated using ISO 6888-1 methods, and antimicrobial susceptibility testing was conducted against three antibiotics: erythromycin, clindamycin, and gentamicin, following CLSI guidelines. Results: Of the 89 samples, 68.5% were contaminated with S. aureus. The highest resistance rates were found for erythromycin (30.5%), with gentamicin showing the lowest resistance (8.3%).No significant correlation (p > 0.05) was found between resistance patterns and fish origin or processing level. Conclusions: The results of this study highlight the widespread occurrence of Staphylococcus aureus in fish sold in the Tri-City area, with a notable prevalence of antibiotic-resistant strains.